Evaluation of the effect of the COVID-19 pandemic on depression, anxiety and psychological resilience in patients with primary immunodeficiency - Anıl Muştucu; Rümeysa Ayşe Güllülü; Sukru Cekic; Sara Sebnem Kilic; Selçuk Kırlı (BMC Immunology)
Abstract Background Primary immunodeficiencies (PIDs) are a group of diseases that develop as a result of primary or congenital malfunction of the immune system and progress with chronic and/or recurrent bacterial, fungal, protozoal and/or viral infections. In this study, we aimed to examine the effects of the COVID-19 pandemic on depression, anxiety levels and psychological resilience in patients with PID and to compare them with those in controls. Methods Seventy patients, aged 18–65 years, who were being followed up with a diagnosis of PID and 69 people as healthy control group, participated in our study. The participants were evaluated cross-sectionally once; sociodemographic data form, Hamilton Depression Rating Scale (HAM-D), Hamilton Anxiety Rating Scale (HAM-A), Resilience Scale for Adults (RSA), and COVID-19 Evaluation form were administered to the participants. Results HAM-A and HAM-D scores were significantly higher in PID patients compared to controls (HAM-D: 5.5 vs. 3.0, p < 0.001; HAM-A: 6.0 vs. 4.0, p = 0.008). RSA was significantly lower in the patient group (RSA total: 122.5 vs. 136.0, p < 0.001), and pandemic-related risk perception was higher (PRPS: 33.9 vs. 28.3, p < 0.001). Sleep, appetite, and attention-related disturbances were also more common in the patient group. Multivariate regression analyses revealed that PID diagnosis was an independent predictor of increased depression severity (HAM-D), lower psychological resilience (RSA), and greater pandemic-related risk perception. Female sex was independently associated with higher anxiety severity (HAM-A). A personal psychiatric history and greater number of comorbidities were also significant predictors of psychological vulnerability, particularly in relation to depression and anxiety. Conclusion Given the observed associations between PID and increased levels of depression, anxiety, and reduced psychological resilience during the pandemic, clinicians may consider heightened vigilance for psychological symptoms in this population during times of public health crisis.